Clinical effectiveness of self-etching adhesives with or without selective enamel etching in noncarious cervical lesions: A systematic review - Wei Qin; Lei Lei; Qi-Ting Huang; Lily Wang; Zheng-Mei Lin (Elsevier, 2014)
Background/purpose: Noncarious cervical lesions (NCCLs) are among the most frequent conditions requiring resin restorations. However, the major shortcoming of these restorations is limited longevity. The purpose of this study was to compare the clinical performance of self-etching (SE) adhesives with or without selective enamel etching in NCCLs. Materials and methods: An initial literature search, with strict inclusion and exclusion criteria, was conducted in MEDLINE, Web of Science, the Wiley Online database, and the Cochrane Controlled Trials Center. Eight trials were included. Restoration retention, prevalence of marginal defects, and marginal discoloration were evaluated. Data were analyzed using the Mantel-Haenszel method with 95% confidence intervals. Results: Results demonstrated that fewer marginal defects (P = 0.0001) and discoloration (P = 0.008) were observed with the selective enamel etching approach. The risk ratio (RR) values of the selective etching group and the nonselective etching group for marginal defects and discoloration were 0.58 (0.44, 0.77) and 0.48 (0.28, 0.83), respectively. For restoration retention, the differences between the two groups were not significant (P = 0.44). The RR values of the selective etching group and the nonselective etching group for restoration retention were 1.01 (0.98, 1.04) and 1.02 (0.96, 1.08), according to a fixed-effects model at 2- and 5-year observation time, respectively. Conclusion: Previous enamel etching resulted in fewer marginal defects and marginal discoloration, compared with using the SE approach alone. For restoration retention, the differences between the two groups were not significant. Additional longer follow ups and large-scale investigations are expected to assess possible advantages of selective enamel etching in NCCL restorations.